(untitled) (Swiss Medical Weekly, 2017)
The opportunistic pathogen Staphylococcus aureus encounters a variety of host defence systems depending on its localisation during colonisation in the nares, systemic infections within the body, or persistent infections within cells or embedded in biofilms. To respond rapidly to these different environments, this bacterium has evolved, in its longstanding interaction with animal and human hosts, a variety of mechanisms to fine-tune its gene expression. RNA metabolism, including transcription, processing, translation into proteins and RNA decay, is a central player in this response and might in the future be used to treat this feared pathogen.